Gold Medallist at 21st International Invention Innovation & Technology Exhibition (ITEX 2010) - UMP, PNC
Researchers at Universiti Malaysia Pahang (UMP) are currently developing an innovative renewable fuel technology, which has the ability to produce a sustainable energy supply from wet waste, such as sewage, leach ate and paper mill waste.